2012
DOI: 10.1371/journal.pone.0038249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Drinking Water Arsenic on Mouse Fetal and Postnatal Growth and Development

Abstract: BackgroundArsenic (As) exposure is a significant worldwide environmental health concern. Chronic exposure via contaminated drinking water has been associated with an increased incidence of a number of diseases, including reproductive and developmental effects. The goal of this study was to identify adverse outcomes in a mouse model of early life exposure to low-dose drinking water As (10 ppb, current U.S. EPA Maximum Contaminant Level).Methodology and FindingsC57B6/J pups were exposed to 10 ppb As, via the dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 42 publications
10
42
0
Order By: Relevance
“…Importantly, NAFLD is estimated to be prevalent in 20-30% of the general population in western countries [56], so understanding the underlying causes for the onset and progression of this disease is essential. In this regard, our results are consistent with previous studies showing that arsenic exposure leads to fatty livers in pregnant female mice [8]. Thus, arsenic may be an important toxicant with particular sensitivity to the developing fetus, predisposing mice to NAFLD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, NAFLD is estimated to be prevalent in 20-30% of the general population in western countries [56], so understanding the underlying causes for the onset and progression of this disease is essential. In this regard, our results are consistent with previous studies showing that arsenic exposure leads to fatty livers in pregnant female mice [8]. Thus, arsenic may be an important toxicant with particular sensitivity to the developing fetus, predisposing mice to NAFLD.…”
Section: Discussionsupporting
confidence: 93%
“…An interesting observation was that the female mice exposed to arsenic IU were significantly underweight during the first two weeks after birth, when compared to their control counterparts. Similarly, Kozul-Horvath et al, showed that female mice that were exposed to 10 ppb arsenic IU, had a delay in weight gain at postnatal day 21 [8]. Our IU arsenicexposed mice showed a full recovery in weight by 4 weeks of age, and no significant changes were observed thereafter.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other investigators have confirmed that micromolar levels of iAs caused DNA damage, cell arrest, and probable reduction of levels of cyclin/CDKs [37,38]. iAs at micromolar levels have public health outcomes in occurrence of cancers and metabolic diseases, endocrine disruption, and altered immune response [39-44]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, drinking water safety has received great concern, since growing evidence indicates that long-term exposure to contaminated drinking water can induce carcinogenicity (Keshavarzi et al 2012), genotoxicity (Rebola et al 2011), and developmental (Kozul-Horvath et al 2012) and reproductive toxicities (Welsch et al 2008). Yangtze River is the longest river in China, and the river basin supports one-third of China's population and contributes about 40 % of the national gross domestic product of China ).…”
Section: Introductionmentioning
confidence: 99%